ANALISIS DISKRIMINAN DALAM MEMPREDIKSI KONDISI KESULITAN KEUANGAN - Trisnaningsih, Sri (Journal of Accounting and Strategic Finance, 2011)
The purpose of this research is to prove that the contribution of the financial ratios of liquidity ratios, activity ratios, solvency ratios, profitability ratios and market ratios simultaneously in classifying the company's financial condition category of healthy and unhealthy. Besides, it also examines the differences in liquidity ratios, activity ratios, solvency ratios, profitability ratios and market ratios between the company's financial condition category of healthy and unhealthy in Indonesia Stock Exchange.The results showed that the first hypothesis is proven true. The evident that the company's financial ratios can be used simultaneously is when it used to classify the category of manufacturing companies financial distress and non-financial distress by using discriminant analysis. The second hypothesis assumed that the financial ratios of liquidity, have contributed in classifying companies in the enterprise category of healthy and unhealthy conditions unverified. It is proven that the three financial ratios that have differences between companies in the category of non-financial distress and financial distress. Whereas, on the six financial ratios do not have differentiate between companies in the category of non-financial distress and financial distress.Keywords : Financial distress, non-financial distress, the analysis descriminan